Pharmacokinetics of CTLA4Ig fusion protein in healthy volunteers and patients with rheumatoid arthritis - Ma Ying; Lin Bi-rong; Lin Bei; Hou Sheng; Qian Wei-zhu; Li Jing; Tan Min; Ma Jian; Li Bo-hua; Wang Hao; Wen Ai-dong; Guo Ya-jun (Acta Pharmacologica Sinica, 2016)
Aim: To evaluate single-dose and multiple-dose pharmacokinetics of cytotoxic T-lymphocyte-associated antigen 4 fusion protein (CTLA4Ig) in healthy volunteers and patients with rheumatoid arthritis (RA). Methods: The clinical trials included two phase I open studies: study 1 was an open-label dose-escalation study in 27 healthy volunteers and study 2 was a single-group, open-label study in patients with rheumatoid arthritis. In study 2, 9 patients were arranged to receive 10 mg/kg of CTLA4Ig at 0, 2, 4, 8, 12, and 16 weeks. The concentration-time data obtained by a validated ELISA method were subjected to non-compartmental pharmacokinetic analysis by DAS 2.1 software. Results: In study 1, serum CTLA4Ig concentrations climbed rapidly to the peak and declined slowly with a t1/2 of 15.1±2.6 d, 14.2±2.3 d, and 11.8±1.2 d after a single infusion of 1, 10, and 20 mg/kg, respectively.Cmax and AUC0–∞ increased proportionally with the dose. In study 2, the steady-state condition for CTLA4Ig following multiple doses of 10 mg/kg appeared to be attained at the fourth dose (d 56), with peak and trough concentrations of 239.8±45.3 mg/L and 20.5±7.9 mg/L, respectively. After multiple infusions, serum concentrations dropped slowly and the terminal half-life was 12.6±4.7 d. Conclusion: Intravenous infusion of CTLA4Ig was well tolerated in healthy volunteers and patients with rheumatoid arthritis. CTLA4Ig exhibited linear pharmacokinetics over the dose range of 1 to 20 mg/kg in healthy volunteers. The pharmacokinetics in RA patients appeared to be similar to that in healthy volunteers. No system accumulation appeared upon repeated infusions of 10 mg/kg every 4 weeks.